Implementasi Kebijakan Parkir Elektronik Melalui Technology Readiness dalam Mewujudkan Smart City di Kota Surabaya - Anita Tri Agustin; Endang Indartuti; Dida Rahmadanik (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to analyze and describe electronic parking policies that can consider the technology readiness factor of the people of Surabaya in order to realize a smart city. This type of research uses qualitative descriptive research, with data collection techniques carried out through observation and interviews. This research uses theory using Jan Merse's theory. The research results explain that the electronic parking policy which can take into account technology readiness factors is overall quite effective, although there are still obstacles that can be overcome with continuous monitoring and evaluation. The implementation of this policy supports the development of smart cities and is expected to improve the quality of life of Surabaya City residents.